2019
DOI: 10.3177/jnsv.65.s80
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ultra-High Hydrostatic Pressurizing Brown Rice on Cognitive Functions and Mental Health of Elderly Japanese Individuals: A 2-Year Randomized and Controlled Trial

Abstract: Brown rice contains many ingredients that might protect against cognitive decline and Alzheimer's disease. However, brown rice is very hard, difficult to cook, and is poorly digested; thus, it is difficult to eat long-term. To solve these problems, ultra-high hydrostatic pressurizing brown rice (UHHPBR) was prepared. We investigated the effects of dietary UHHPBR administration for 24 mo on cognitive function and mental health in the elderly. Healthy elderly participants (n552) were randomized into UHHPBR and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 40 publications
3
31
0
Order By: Relevance
“…This is in line with other studies on this research topic (Vauzour et al, 2017;Calil et al, 2018;Kita et al, 2018;Mazza et al, 2018;Solfrizzi et al, 2018;Chen et al, 2019;Cremonini et al, 2019;Dodd et al, 2019). Furthermore, the findings reveal that healthy diet and healthy diet components might have effects on specific cognitive domains, such as memory in general (Chai et al, 2019;Karstens et al, 2019), episodic memory (Okubo et al, 2017;Marseglia et al, 2018;Whyte et al, 2018), or processing speed (Kuroda et al, 2019). Better memory performance influenced by targeted nutrition interventions was also mentioned in previous research studies, e.g., Kulzow et al (2016), whose intervention was based on the omega-3 fatty acid supplementation.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This is in line with other studies on this research topic (Vauzour et al, 2017;Calil et al, 2018;Kita et al, 2018;Mazza et al, 2018;Solfrizzi et al, 2018;Chen et al, 2019;Cremonini et al, 2019;Dodd et al, 2019). Furthermore, the findings reveal that healthy diet and healthy diet components might have effects on specific cognitive domains, such as memory in general (Chai et al, 2019;Karstens et al, 2019), episodic memory (Okubo et al, 2017;Marseglia et al, 2018;Whyte et al, 2018), or processing speed (Kuroda et al, 2019). Better memory performance influenced by targeted nutrition interventions was also mentioned in previous research studies, e.g., Kulzow et al (2016), whose intervention was based on the omega-3 fatty acid supplementation.…”
Section: Discussionsupporting
confidence: 90%
“…The findings indicate that the described dietary and single nutrient interventions had a positive effect on global cognition (Marseglia et al, 2018;Moran et al, 2018), specifically on memory performance (Chai et al, 2019;Karstens et al, 2019), processing speed (Kuroda et al, 2019), and episodic memory (Okubo et al, 2017;Marseglia et al, 2018;Whyte et al, 2018). One study (Moran et al, 2018) reported a minor effect, and that concerned a reduced task completion time in the followup periods, revealing improved performance.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…On one hand, at the time of writing this manuscript, there were no active intervention studies on human subjects on cognitive ability, except for a few studies [ 29 , 30 ]. For instance, in the study by Uenobe et al (2019), elderly people living in an elderly welfare facility were divided into two groups, and brown rice or white rice was ingested three meals a day for six months.…”
Section: Introductionmentioning
confidence: 99%